BENTUK WANPRESTASI DALAM PERJANJIAN PENDAHULUAN PELAKSANAAN JUAL BELI RUMAH PADA PENGELOLA PERUMAHAN PANDAN HARUM - Nurhalimah Nurhalimah (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACTRegarding the implementation effort in the preliminary agreement PT.Pengelola Housing Pandan Harum Tamara , both first -party and second party has been trying to implement the rights and obligations of each . Preliminary agreement regarding the sale of the house in general , based on Article 1338 of the Civil Code which states " All approvals are made legally valid as the law for those who make agreements that can not be reimbursed in addition to the agreement of both parties , or for the reasons stated by the law enough for the agreements to be implemented in good faith . Then the particulars of preliminary agreements stipulated in the Decree of the Minister of Housing Number : 09/KPTS/M/1995 on Guidelines for Sale and Purchase Homes In The Decree does not explicitly mention the definition of the preliminary agreement , but it can only be concluded that the preliminary agreement is agreements made before the house was completed.